Comparative Analysis of Lead Ions and Ammonium Salts in Malachite Sulfurization-Assisted Flotation Based on Surface Layer Durability - Ayman M. Ibrahim; Han Wang; Peilun Shen; Dianwen Liu (Metals, 2025)
Sulfurization-assisted flotation is a key process that uses sulfur compounds to modify mineral surfaces, enhancing hydrophobicity and flotation efficiency, especially for copper oxide minerals. This study introduced the preliminary activation of malachite utilizing a combination of Pb2+ and NH4+ ions in sulfurization systems, significantly improving flotation recovery. Flotation tests and surface analysis techniques were employed to examine the effects of Pb2+ and NH4+ ions on malachite’s flotation behavior and the stability of its sulfurized surface layer. The results showed that, after activation with Pb2+ and NH4+ at optimal reagent concentrations, malachite’s flotation recovery reached 94.6%, compared to 68.13% with traditional sulfurization. Atomic force microscopy (AFM) revealed significant changes in malachite’s surface morphology, with a dense, cloud-like sulfide film forming that contained more sulfur than in direct sulfurization, enhancing the durability of the sulfurized surface. Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS) analysis confirmed increased sulfide ion adsorption on the surface compared to traditional sulfurization. The Pb2+ + (NH4)2S + Na2S system generated numerous active sites from copper-sulfide species, promoting the growth of sulfurized phases. FT-IR analysis showed stable Cu-S species on the malachite surface, improving SBX adsorption and flotation performance. Contact angle measurements indicated that the activation systems significantly improved surface hydrophobicity, with the copper-sulfide film achieving a contact angle of 95.29°, demonstrating superior durability and mineral recovery compared to traditional sulfurization. Thus, the activation of Pb2+ and NH4+ ions offers a promising solution for sulfurization-assisted flotation, enabling more efficient and sustainable recovery of malachite ore, with improved sulfide layer durability and enhanced hydrophobicity.